Effect of Zinc Nano Fertilizer on the Growth of Spinach (Spinacea Oleracea L.) (International Journal of Scientific Research in Science and Technology, 2024)
The field experiment was conducted during summer season in India with five different treatment combinations; Current experiment was laid out in order to compare different kinds of vermicompost and chemical fertilizers including nano fertilizer application in growing spinach under the open-field conditions. The result revealed that growth in term of number of leaves, plant height, leaf area, leaf yield and leaf quality. The growth performance in respect of plant height, numbers of leaves and leaf area were found to be maximum in through Zinc nanoparticles but which was found to be at far with vermicompost. Considering the aforesaid issue, a pot experiment was conducted to assess the performance of fertilizers on growth, yield and height of Spinach (Spinacea oleracea Linn) with treatments zinc nanoparticles (T1), mix zinc boron (T2), zincate (mix zinc, phosphate, sulphate) (T3), Vermicompost (as feed) (T4) and without any fertilizers (T5) were organized in garden. The experiment was a completely randomized design during 45 days.